2020
DOI: 10.7554/elife.56235
|View full text |Cite
|
Sign up to set email alerts
|

The identification of dual protective agents against cisplatin-induced oto- and nephrotoxicity using the zebrafish model

Abstract: Dose-limiting toxicities for cisplatin administration, including ototoxicity and nephrotoxicity, impact the clinical utility of this effective chemotherapy agent and lead to lifelong complications, particularly in pediatric cancer survivors. Using a two-pronged drug screen employing the zebrafish lateral line as an in vivo readout for ototoxicity and kidney cell-based nephrotoxicity assay, we screened 1280 compounds and identified 22 that were both oto- and nephroprotective. Of these, dopamine and L-mimosine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 109 publications
(156 reference statements)
3
8
0
Order By: Relevance
“…23 Uncontrolled hypertension leads to high intra-glomerular pressure, which damages the blood vessels in the kidney, thus damaging glomeruli and resulting in reduced GFR. 34 Our study revealed that adult cancer patients who received platinum agents were two times likely to develop nephrotoxicity than those who received other treatment regimens, a finding similar to other studies done in Switzerland, 31 Canada, 35 Brazil, 36 and Ethiopia. 37 The high prevalence of nephrotoxicity among adult cancer patients who received platinum agents may be due to the preventive strategies used where hydration with normal saline and administration of magnesium sulphate were the preventive measures for nephrotoxicity.…”
supporting
confidence: 89%
“…23 Uncontrolled hypertension leads to high intra-glomerular pressure, which damages the blood vessels in the kidney, thus damaging glomeruli and resulting in reduced GFR. 34 Our study revealed that adult cancer patients who received platinum agents were two times likely to develop nephrotoxicity than those who received other treatment regimens, a finding similar to other studies done in Switzerland, 31 Canada, 35 Brazil, 36 and Ethiopia. 37 The high prevalence of nephrotoxicity among adult cancer patients who received platinum agents may be due to the preventive strategies used where hydration with normal saline and administration of magnesium sulphate were the preventive measures for nephrotoxicity.…”
supporting
confidence: 89%
“…Interestingly, we found that exogenous DA also protects from cisplatin-induced neuronal damage. Similar findings have been reported in Zebrafish model, in which high DA levels (or alternatively L-miosine) not only protect from ototoxicity but also from nephrotoxicity induced by cisplatin but without affecting the toxicity in tumoral cells (Wertman et al, 2020). Although further experiments are needed to unravel the mechanisms beyond such protectiveness, there are two hypotheses to explain why increased DA levels mediate oto- and nephroprotection.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, we found that exogenous DA also protects against cisplatin-induced animal locomotion and posture alterations, presumably caused by DA signaling perturbations because dopaminergic neuron integrity is not affected. Similar findings have been reported in a zebrafish model, in which high DA levels (or alternatively L-mimosine) not only protect against ototoxicity but also nephrotoxicity induced by cisplatin, without affecting the toxicity in tumoral cells ( Wertman et al, 2020 ). Although further experiments are needed to unravel the mechanisms beyond such protectiveness, there are two hypotheses to explain why increased DA levels mediate oto- and nephroprotection.…”
Section: Discussionsupporting
confidence: 86%